2005
DOI: 10.1242/jeb.01868
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional analysis of mussel taurine transporter, as a key molecule in cellular osmoconforming

Abstract: intensive expression of muTAUT was observed in the gill and epithelium of the mantle, which were directly exposed to intensive osmotic changes of ambient seawater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 43 publications
(53 reference statements)
1
55
0
Order By: Relevance
“…By interfering with the epithelial absorption of the nutrient, these substances can be classified as anti-nutritional factors. TauT was described in mammals (Bedford et al, 2000), chicken (Kim et al, 2006), common carp and tilapia (Takeuchi and Toyohara, 2000), S. senegalensis (Pinto et al, 2011), and mussels (Hosoi et al, 2005); hence it is likely that such anti-nutritional action of substances such as β-amino acids would be conserved in fish. Results suggest an interaction between taurine and other anti-nutritional factors, as illustrated by the restorative effects of cholyltaurine on saponin-and lectin-induced enteritis Iwashita et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…By interfering with the epithelial absorption of the nutrient, these substances can be classified as anti-nutritional factors. TauT was described in mammals (Bedford et al, 2000), chicken (Kim et al, 2006), common carp and tilapia (Takeuchi and Toyohara, 2000), S. senegalensis (Pinto et al, 2011), and mussels (Hosoi et al, 2005); hence it is likely that such anti-nutritional action of substances such as β-amino acids would be conserved in fish. Results suggest an interaction between taurine and other anti-nutritional factors, as illustrated by the restorative effects of cholyltaurine on saponin-and lectin-induced enteritis Iwashita et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, recent studies have confirmed that taurine has a wide variety of biological functions including maintaining homeostasis and regulating physiological functions of different systems. Taurine also possesses a wide spectrum of pharmacological activities such as antipyretic, anticonvulsant, antiplatelet-aggregation, hypotensive, immunity-enhancing, liver-protecting and angiotasisregulating effects [10][11][12][13][14][15][16][17] . It is known that the liver is the main www.wjgnet.com organ for taurine biosynthesis and also an important target organ for taurine's many biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that the presence of free taurine (or other amino acids) in neurons is not, in and of itself, evidence for its being a neurotransmitter. Taurine is an important osmoregulator in many vertebrates (Schaffer et al 2000;Warskulat et al 2004) and invertebrates (Yin et al 2000;Hosoi et al 2005) and it and b-alanine have been implicated as osmoregulators in cnidarians (Walther 2002). Its presence in cnidarian neurons is, therefore, not altogether unexpected.…”
Section: Discussionmentioning
confidence: 99%